The Narrative of Rape in Genesis 34: Interpreting Dinah's Silence. By Caroline Blyth - Southwood, Katherine (The journal of theological studies, 2011)
Blyth, who has a background in mental health nursing, draws on a number of modern accounts of female experiences of rape in order to give Dinah, who is voiceless within the biblical text, a voice. Blyth supplies this voice through selecting quotations from interviews with modern victims of rape, and examining their feelings after the incident and in relation to the reaction of their close kin., The book has numerous strengths. The initial chapter concerning ‘rape myths’ is well researched and evocative. Blyth has devoted a great deal of time to data collection, as is clear from the range of cross-cultural evidence which is cited. As such, the chapter successfully illustrates the similarities between the responses of rape victims, and their families, within the reports.